(untitled) - Kato, Hiroki (New Jersey, 1992)
This work offers guidance on how to break through the potential cultural barriers that could hamper business dealings with Japan. The book explains the nuances of Japanese etiquette, entertainment, non-verbal language, style of decision-making and power play. It illuminates the Japanese mind set, including patterns of thought and philosophy. It also provides an understanding of Japanese protocol, from how to give and receive compliments to the Japanese sense of time and timing. Each topic is discussed in the light of its direct impact on conducting business and numerous anecdotes involving political and business leaders are included.
Keywords: Business communication,Giao tiếp kinh doanh; Japan,Nhật Bản